“Yong, and the unworthiest of thousands”: Youth and Subjectivity in Shakespeare and Speght - Prusko, Rachel (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
This article explores youthful subjectivity in both dramatic and non-dramatic verse, considering representations of female youth in Shakespeare’s late romance Pericles alongside the work of poet and polemicist Rachel Speght. The complex, unstable category of youth contributes both to Shakespeare’s rendering of his fourteen-year-old female character in his play and to Speght’s portrayal of herself in her poetry. Shakespeare’s Marina narrates her own tale and reconstitutes narratives spun about her, creating space for youthful self-fashioning. Nineteen-year-old Speght undertakes a similar project of self-making in her prose treatises and particularly in her two published poems, “A Dreame” and Mortalities Memorandum. This article compares self-fashioning in the work of a young female writer to the construction of the young female self by a contemporary male writer, suggesting that youthful subjectivity inheres for both girls in principles of authorship and narrative authority.